Natural Language Processing (NLP) Sophistication on Financial Reporting in the State-Owned Banks in Medan City - Yola Yolanda; Fenny Julistine Tarigan; Iskandar Muda (International Journal of Management, Economic and Accounting, 2026)
The increasing application of Natural Language Processing (NLP) has transformed financial reporting practices through the automation of narrative disclosure analysis and regulatory document processing. Although NLP adoption has become more widespread in the banking sector, empirical evidence on how the level of organizational information technology maturity influences the effectiveness of NLP in financial reporting remains limited, particularly in developing countries. Grounded in IT Capability Theory, this study aims to examine the effects of four dimensions of IT sophistication, namely informational sophistication, technological sophistication, functional sophistication, and managerial sophistication on financial reporting in state-owned banks in Medan City. This study employs survey data collected from employees of state-owned banks and analyzes the data using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The findings reveal that the impact of IT sophistication on financial reporting is not uniform. Functional sophistication and managerial sophistication are found to have a positive and significant effect on the quality of financial reporting, while informational sophistication and technological sophistication do not exhibit a significant effect at the 5% significance level. These results indicate that the strategic value of NLP in financial reporting can only be realized when the technology is effectively integrated into core business processes and supported by adequate governance structures and managerial commitment. This study contributes empirical evidence to the development of IT Capability Theory within the context of NLP implementation in the banking sector of developing countries. From a practical perspective, the findings underscore the importance of strengthening functional integration and managerial roles in NLP-based digital transformation strategies for financial reporting.